Development and driving of the national disease and health hazard prevention and control plan towards a robust disease and health hazard prevention and control system - Siripuchaka, Puckanee; Kaewsombat, Natthawut; Tanakitpiboon, Pavinee; Bunngamchairat, Ariya (Disease Control Journal, 2025)
The qualitative study aimed to analyze the review and development process of the 20-year national development plan for the prevention and control of diseases and health threats (2018-2037), revised version 2021, and the second phase of the national action plan, the strengthening phase (2023-2027). The study also examined the mechanisms for implementing the action plan, identified key success factors and obstacles, and provided policy and practice recommendations to facilitate the development and advancement of the plan toward a robust system of disease and health threat prevention and control. A mixed-method qualitative approach was adopted, integrating document reviews, secondary data analysis, and engagement in meetings with purposefully selected key stakeholder groups. The findings revealed that three critical processes were Identified: preparing the relevant information, communicating the conceptual framework and methodologies for reviewing and improving the plan to key stakeholders, and organizing the plan review and improvement process through the application of strategic foresight framework. The mechanisms to drive the action plan into practice existed which included policy and legal mechanisms, technical mechanisms, management mechanisms, and monitor and evaluation mechanisms. The need to strengthen the linkage of information on disease prevention, control, and health threats with both internal and external networks as well as the lack of evaluation regarding the efficiency of these mechanisms in driving the plan forward should be highlighted. For policy recommendations, the formulation of strategies, especially in areas of disease prevention and control and health threats, should emphasize the use of technology and analytical tools to manage big data. This is to design responsive disease prevention and control service systems to meet public needs and ensure preparedness for future challenges. For practical recommendations, the integration of multiple principles under PDCA cycle should be employed to guide the development of sustainable implementation mechanisms and the initiation of a sandbox project for innovation